Reviewing Canada's monetary policy implementation system: Does the evolving environment support maintaining a floor system? - Toni Gravelle; Ron Morrow; Jonathan Witmer (Bank of Canada, 2023)
At the onset of the pandemic, the Bank of Canada transitioned its framework for monetary policy implementation from a corridor system to a floor system, which it has since decided to maintain. This decision was informed by the analysis and assessment of the two frameworks in this paper. We provide a comprehensive analysis of both frameworks and assess their relative merits based on five key criteria that define a sound framework. Our evaluation includes a discussion of how these relative merits have changed since the pandemic began. Specifically, we examine the evolving regulatory landscape, changes in payment systems, and the Bank's quantitative easing program to understand their implications for the relative strengths of the two frameworks for monetary policy implementation.
Keywords: D4; D47; E42; E5; E58; 330; Monetary policy implementation; Payment clearing and settlement systems; Market structure and pricing